The search of the effectiveness of human rights: an analysis of the city of millennium goals Aquiraz (Ceará, Brazil) - Renato ALVES VEIRA DE MELO (Revista de Estudios Brasileños, 2016)
The purpose of this paper is to help understand and recognize the current conjunction of the Millennium Aims focused on the poverty and the education in the town of Aquiraz. With this perspective, this work shows the use of the chosen strategies in the town to reach the Millennium Aims, specifically focused in reducing poverty and in the basic education, showing the methods used by the State of Ceará together with the town of Aquiraz for achieving their targets within an economical growth, presenting the achievements as well as what it is yet to be done in order to reach and fulfill the ODM’s objectives. The planet cannot hold the intensive use of the unsustainable natural resources any more, and the Sustainable Development Aims need to draw the specific way towards a model of sustainable development, starting from the agreements got between the countries at the Conference for the Sustainable Development happened in 2012, Rio+20.